2007
DOI: 10.1097/01.mlg.0000246953.44163.81
|View full text |Cite
|
Sign up to set email alerts
|

Submandibular Gland Transfer for Severe Xerophthalmia

Abstract: Microvascular submandibular gland transfer is an effective approach for correcting severe xerophthalmia. The procedure should be within the skills of any reconstructive microsurgeon. This procedure offers a unique opportunity for otolaryngologist-head and neck reconstructive surgeons to help restore vision to this unfortunate group of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
27
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 12 publications
1
27
0
Order By: Relevance
“…Autologous microvascular transplantation of the submandibular gland (SMG) has proven to be an effective treatment for patients with severe KCS. [1][2][3][4][5][6][7][8][9][10] In our experience of SMG transplantation in 180 patients (195 glands), all viable transplanted SMGs retain their secretion function in the long term and the symptoms of dry eye are greatly relieved. 3,8 However, excessive secretion, or epiphora, occurs in more than 40% of patients at >6 months after surgery.…”
mentioning
confidence: 99%
“…Autologous microvascular transplantation of the submandibular gland (SMG) has proven to be an effective treatment for patients with severe KCS. [1][2][3][4][5][6][7][8][9][10] In our experience of SMG transplantation in 180 patients (195 glands), all viable transplanted SMGs retain their secretion function in the long term and the symptoms of dry eye are greatly relieved. 3,8 However, excessive secretion, or epiphora, occurs in more than 40% of patients at >6 months after surgery.…”
mentioning
confidence: 99%
“…[5][6][7][8][9][10]16,17 Improvement of both subjective symptoms and objective parameters has been verified in long-term follow-up with the procedure. [6][7][8]10 Secretion of the transplanted SMG is used as a substitute for natural tears. Schirmer test, being the most commonly used test to measure tear production, has been used to measure secretion of the transplanted SMG.…”
Section: Discussionmentioning
confidence: 99%
“…This procedure has been effective for severe cases of KCS. [5][6][7][8][9][10] Clinical results showed that the secretions from all viable transplanted SMGs maintained stable function in the long term. 11 The uncomfortable symptoms were relieved, and the frequency of use of pharmaceutical tear substitutes was reduced.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1,[5][6][7][8] This procedure could offer a permanent autologous source of tears with the basal secretion of a transplanted revascularized but denervated submandibular gland and so overcome gustatory epiphora. However, the surgical procedure was complicated, and a perfect microsurgical technique was needed.…”
mentioning
confidence: 99%